Linking inside and outside: "identity" in crisis situations. Issue 4 (1st July 2019) - Battaglia, Massimo; Zhou, Shanshan; Frey, Marco
Abstract : Purpose: The purpose of this paper is to deal with the link between identity and crisis deriving by natural disasters, exploring the function of the shared identity linking individuals, groups, organizations and its external networks. The shared identity is not static. It is a dynamic self-reflexive learning process and is reciprocal. The object of the research is a medium-sized multi-utility company, which experienced the 2012 earthquakes, and how responsibly and rapidly it responded and recovered in collaboration with its stakeholders in the local territory. Design/methodology/approach: Semi-structured interviews were directed to both managers and to selected representatives of the "vertical external networks" of the company (local authorities, a consumer association and a trade association). The primary data were supplemented by archived materials for data triangulation. Findings: The research highlights the importance of identity and relationship with local stakeholders and communities when facing the earthquakes. Believing themselves to be socially responsible, ethical and capable, employees were highly motivated and collaborative. Resuming normal services was AIMAG's priority. The behavior of AIMAG, its employees and its local stakeholders were guided by a shared community identity. After the earthquakes, this shared community identity was strengthened, thus improving the community's resilience. Originality/value: The paper highlights the role of identity in linking both inside and outside an organization, in contributing greatly to joint decision making and action, and, finally, in increasing the awareness of the company leaders and staff regarding the importance of their actions for the whole local community. This research advocates the role of identity in disaster risk reduction.